PELAYANAN PERIZINAN DALAM PENGURUSAN SURAT IZIN MENDIRIKAN BANGUNAN (IMB) DI DINAS TATA RUANG DAN BANGUNAN KOTA PEKANBARU TAHUN 2012-2014 - Mukhridal "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Service is an implementation of the rights of the people or consumers within the life of the state and society, in the organization of such services as mandated in Decision Regulation No. 24 of 2006 on public services is expected to service the fast, precise, easy, accurate, inexpensive and affordable by the community as consumer. But in reality it is still within the contextual concept that did not move away from long bureaucratic structure, which takes a lot of time and higher costs. Besides, there are factors that affect service delivery as well as in theory Edwards III, Communications, Resources, Attitudes and Structures Bureaucracy.In the implementation of the licensing service on Spatial Planning and Building Pekanbaru not run optimally, there are still shortcomings in its implementation so that people do not get the best services from the Agency. Among these problems is a process, time and cost penyelenggaraaan. And in the provision of services on the disclosure of information that is needed by the community is not available as expected, causing society finds it difficult to get public information services.In response to this problem, the researchers conducted a study on the creation of Licensing Services Building Permit (IMB) at the Department of Spatial Planning and Building Pekanbaru City in 2012 - 2014. The research is a qualitative research with descriptive approach. The population in this study is the apparatus as a community service providers and consumers. Data was collected by means of literature review, observation and direct observation of the object of study, as well as interviews with respondents and informants.Based on the results of this research is expected Spatial Planning and City Buildings Pekanbarudapat run licensing services are excellent and professional, with information that is easily accessed by the public Yag entitled to the provision of services licensing quality, and to optimize service resources in order to be empowered in accordance with the management capabilities and organization of the agency. So that the implementation is in accordance with good governance (good governance).Keyword: Service, Licensing, Services Building Permit (IMB)